2007
DOI: 10.1038/sj.onc.1210891
|View full text |Cite
|
Sign up to set email alerts
|

The proapoptotic effects of sulindac, sulindac sulfone and indomethacin are mediated by nucleolar translocation of the RelA(p65) subunit of NF-κB

Abstract: Understanding the mechanisms that underlie the antitumour activity of non-steroidal anti-inflammatory drugs (NSAIDs) against colorectal cancer will allow the development of more effective and specific chemopreventative agents. Modulation of the NF-jB pathway has been implicated as a key effector of the antitumour effect of aspirin, but the effects of non-aspirin NSAIDs on this pathway have yet to be fully defined. Here, we demonstrate that sulindac, sulindac sulfone and indomethacin activate the NF-jB pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…One post-induction mechanism that we have identified for regulating NF-κB transcriptional activity and apoptosis is the nuclear/nucleolar distribution of RelA. We have shown that in response to specific stress-inducing stimuli, including UV-C radiation, serum deprivation, and aspirin and related agents, RelA translocates from the cytoplasm to the nucleoplasm and then to the nucleolus (11)(12)(13). We identified a signal at the NH 2 terminus of RelA [amino acids (aa) [27][28][29][30] that is required for nucleolar translocation of the protein and showed, using a dominant-negative mutant deleted for this domain, that nucleolar translocation of RelA is causally involved in the downregulation of NF-κB-driven transcription and the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…One post-induction mechanism that we have identified for regulating NF-κB transcriptional activity and apoptosis is the nuclear/nucleolar distribution of RelA. We have shown that in response to specific stress-inducing stimuli, including UV-C radiation, serum deprivation, and aspirin and related agents, RelA translocates from the cytoplasm to the nucleoplasm and then to the nucleolus (11)(12)(13). We identified a signal at the NH 2 terminus of RelA [amino acids (aa) [27][28][29][30] that is required for nucleolar translocation of the protein and showed, using a dominant-negative mutant deleted for this domain, that nucleolar translocation of RelA is causally involved in the downregulation of NF-κB-driven transcription and the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, we described an alternative mechanism for this repression involving nucleolar sequestration of RelA. 13,14 We demonstrated that upon stimulation of the NF-kB pathway by specific stresses (including UV-C radiation, serum deprivation, cyclin-dependent kinase 4 inhibition and aspirin/related agents) the RelA component of NF-kB translocates from the cytoplasm to the nucleoplasm and then to the nucleolus. 13,15 We identified a signal at the N-terminus of RelA (aa [27][28][29][30] that was essential for nucleolar translocation of the protein and, using a dominant negative mutant deleted for this domain (green fluorescent protein (GFP)-RelADNoLS), demonstrated that nucleolar sequestration of RelA is causally involved in the repression of NF-kB-driven transcription and the induction of apoptosis.…”
mentioning
confidence: 99%
“…Sulindac sulfone is clearly yet another multifunctional drug. Both sulindac sulfide and sulindac sulfone are effective inducers of apoptosis and effective preventive agents in animal models of intestinal neoplasia (14,15,18,19).…”
mentioning
confidence: 99%